Stability properties and microstructure properties of microwave-sintered CeO2 doped zirconia ceramics. Issue 20 (15th October 2021) - Ling, Yeqing; Hao, Xiandong; Gui, Yuxi; Qiu, Hongju; Li, Qiannan; Zheng, Hewen; Omran, Mamdouh; Gao, Lei; Chen, Jin; Chen, Guo
Abstract: Nanosized CeO2 –ZrO2 powders prepared by atmospheric pressure pyrolysis were used as raw materials to prepare CeO2 –ZrO2 ceramics using microwave sintering. The samples were characterised using bulk density measurements, X-ray diffraction (XRD), Fourier Transform Infrared Spectrometer (FT-IR), Raman, and scanning electron microscopy (SEM). The purpose was to determine the optimised microwave sintering process for CeO2 –ZrO2 ceramics and reveal the corresponding mechanism. The results show that with a CeO2 addition content above 5 mol%, the tetragonal phase peak appeared obviously in the sample. The results show that the tetragonal phase peak appears when the CeO2 content is more than 5 mol%. The dopants, namely CeO2, have reduced the solid solution's phase transformation temperature with the assistance of microwave heating. Additionally, the grain size of the CeO2 –ZrO2 ceramics has shown a negative relationship with Ce content at a temperature of 900 °C. The reason is that the rapid sintering due to microwave sintering and the oxygen vacancies generated by CeO2 can effectively inhibit grain growth. The regulation mechanism on microwave sintering of CeO2 –ZrO2 ceramic was clarified, and the technical prototype of controlled prepared CeO2 –ZrO2 ceramics by microwave sintering was constructed.